Using the Hermeneutic Phenomenological Method to Explore the Middle School Student Lived Experience of Student Driven Inquiry - Buchanan, Shelly C. (Qualitative and Quantitative Methods in Libraries, 2019)
This paper discusses a hermeneutic phenomenological exploration of the lived experience of middle school students (ages 13-14) engaged in student driven inquiry (SDI), an inquiry based learning (IBL) approach in which students engage in self-determined study, content creation, and findings presentation. Eight common themes of SDI experience emerged: Autonomy, Academic Challenges, Motivation & Engagement, Understanding Research as Fundamental, Satisfaction/Enjoyment, Stress, Support, and Expertise. Together these 8 themes reveal middle school student appreciation for the challenge of the SDI learning approach that embodies excitement, stress, learning, struggle, and ultimately feelings of achievement in what students consider worthy work that prepares them for future academic and life experiences. The narrative student perspective of SDI experience adds important new information to the existing literature on K-12 information literacy practices, information experience, inquiry-based learning models, and student motivation. Next steps for SDI framework development and continued related research are discussed.